2008
DOI: 10.1016/j.epsl.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Mixing in the solar nebula: Implications for isotopic heterogeneity and large-scale transport of refractory grains

Abstract: The discovery of refractory grains amongst the particles collected from Comet 81P/Wild 2 by the Stardust spacecraft (Brownlee et al. 2006) provides the ground truth for large-scale transport of materials formed in high temperature regions close to the protosun outward to the comet-forming regions of the solar nebula. While accretion disk models driven by a generic turbulent viscosity have been invoked as a means to explain such large-scale transport, the detailed physics behind such an "alpha" viscosity remain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 42 publications
5
52
1
Order By: Relevance
“…And third, the isotopic composition of condensed (i.e., rocky) matter in the solar system is defined entirely by a mixture of supernova plus nova plus red giant grains. This scenario may be consistent with intermittent phases of gravitational instability in the gaseous disk (38).…”
Section: Nebula-wide Mass Transport Of Materialssupporting
confidence: 74%
See 1 more Smart Citation
“…And third, the isotopic composition of condensed (i.e., rocky) matter in the solar system is defined entirely by a mixture of supernova plus nova plus red giant grains. This scenario may be consistent with intermittent phases of gravitational instability in the gaseous disk (38).…”
Section: Nebula-wide Mass Transport Of Materialssupporting
confidence: 74%
“…37) suggested that particle diffusion within the disk itself led to grains being transported significant distances outward from the Sun over time scales of 0.1 to 1 Myr. Boss (38) showed that a phase of marginal gravitational instability is able to rapidly transport small particles from the inner disk to the outer disk while simultaneously homogenizing most initial isotopic heterogeneity, over time scales less than 0.001 Myr. It is possible that all three mechanisms operated in transporting grains outward from the Sun, but results from the Stardust sample return mission from Comet Wild 2 comet dust may pose a problem for the disk diffusion model.…”
Section: Nebula-wide Mass Transport Of Materialsmentioning
confidence: 99%
“…Heating to temperatures greater than 1100 K can anneal silicates to crystallinity, but no protoplanetary heating sources have been identified that were sufficiently strong to heat materials in the outer nebula, where comets are believed to form, to such high temperatures. Possible explanation scenarios reinforced the conclusion that large-scale mixing indeed played a key role in the small bodies' formation in the protoplanetary disk (Bockelée-Morvan et al 2002;Boss 2008).…”
Section: Introductionmentioning
confidence: 54%
“…The only reported magnesium isotopic compositions of the 16 O-rich micron-sized corundum grains from Murchison (Virag et al 1991) are consistent with their early formation. Although the exact mechanism of radial mixing remains controversial (Shu et al 1996(Shu et al , 1997Bockelée-Morvan et al 2002;Gail 2001Gail , 2004Dullemond et al 2006;Ciesla 2007;Boss 2008), it was probably most effective at transporting materials outward at the very earliest stages of disk evolution, when the rates of mass and angular momentum transport are at their highest, allowing for the large-scale redistribution of disk materials.…”
Section: Resultsmentioning
confidence: 99%